Zwyrodnienie barwnikowe siatkówki – przebieg kliniczny, diagnostyka i możliwości leczenia - Grześk, Magdalena; Malukiewicz-Wiśniewska, Grażyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The purpose of this study was to evaluate clinical course of retinitis pigmentosa taking into consideration models of inheritance and possible treatment. Retinitis pigmentosa belongs to heterogeneous group of hereditary disorders, which are connected with gradual loss of the photoreceptor function, firstly rod cells subsequently cones, which is accompanied by the retinal pigmentary epithelium disorder. Retinitis pigmentosa connected with X chromosome is one of the most severe form of this disease that in polish population takes place with frequency at average 10-15% which is similar to ADRP – 10-20% . Course of RP, despite many similarities may differ from each other and prognosis depends on model of inheritance. Unfortunately, in spite of many efforts, nowadays medicine do not have successful treatment for patients with RP.